Evaluation of the Accuracy of Extraction of Slope and Length Based on DEM of GF-7 Satellite - ZHAO Yunlong; FU Suhua (Shuitu Baochi Xuebao, 2024)
[Objective] Slope and slope length are essential topographic factors, and their calculation accuracy directly affects the evaluation accuracy of slope soil erosion model. The high-precision elevation measurement capability of Gaofen-7 satellite has great potential in the accurate extraction of terrain factors, and it is expected that it can be used in the extraction of slope and slope length to achieve accurate expression of terrain. It is necessary to evaluate the accuracy of the results of slope length extraction using the DEM of Gaofen-7 satellite. [Methods] The slope and slope length of DEM generated by Gaofen-7 satellite, 1∶10 000 topographic map and LiDAR images in 4 small basins in Wubu County, Shaanxi Province were extracted by using the terrain factor (LS) calculation tool. Correlation coefficient (r), relative deviation (RE) and absolute deviation were used as evaluation indexes to evaluate the accuracy of extraction of topographic factors by Gaofen-7. [Results] Compared with the slope and slope length of LiDAR and 1∶10 000 topographic map, the average slope extracted by GF-7 was 7.50%～9.02% lower, and the slope length was 1.83%~19.35% larger. However, the area distributions of slope length and slope derived from the three data sources had no significant difference. Comparing the results of slope and slope length, the discrepancy in slope (RE: 16.46%～44.26%) derived from different sources is significantly lower than that (RE: 75.25%～140.87%) was slope length. The discrepancy between different sources was enhanced in gully areas (RE of slope 15.48%～56.63%, slope length: 50.02%～130.79%), while being decreased in inter-gully areas (RE of slope 21.28%～63.61%, RE of slope length 93.01%～192.51%). [Conclusion] It was feasible to obtain areal grading characters of slope or slope length and slope of specified locations using DEMs generated from Gaofen-7 satellite, while the results of slope length for specified locations were less reliable. In conclusion, the Gaofen-7 satellite had a great advantage in describing the spatial distribution of slope length and slope at the watershed scale, while being less capable of capturing slope length and slope at a specific site.